2019
DOI: 10.1016/j.joule.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Polymer Solar Cells Based on Non-fullerene Acceptors with Potential Device Lifetime Approaching 10 Years

Abstract: Organic solar cells (OSCs) based on non-fullerene acceptors (NFAs) have developed very fast in recent years. A proper balance among power conversion efficiency (PCE), stability, and production cost needs further elaboration. Here we investigate the industrial viability of highly efficient OSCs based on several representative NFAs. The most stable OSCs exhibit PCE of $8% along with extrapolated T 80 lifetime (80% of the initial PCE) of over 11,000 hr under equivalent 1 sun illumination, which would lead to a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
386
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(417 citation statements)
references
References 39 publications
7
386
0
2
Order By: Relevance
“…These observations from the R-SoXS and GIWAXS measurements, as well as the shape of the degradation graphs suggest that indeed demixing and crystallization occur at the same time. [59,75] We speculate that the good stability may result from either of two reasons: (i) The system is ideal-miscible, the initial optimized blend has mixed domains that are locally at thermodynamic equilibrium determined by the ideal miscibility, and crystal-free; (ii) The blend is vitrified. Given that the demixing is not extensive and still far from the thermodynamic limit, and that we also see deterioration in FF (to be discussed more fully below), we conclude that crystallization is a strong contributing factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations from the R-SoXS and GIWAXS measurements, as well as the shape of the degradation graphs suggest that indeed demixing and crystallization occur at the same time. [59,75] We speculate that the good stability may result from either of two reasons: (i) The system is ideal-miscible, the initial optimized blend has mixed domains that are locally at thermodynamic equilibrium determined by the ideal miscibility, and crystal-free; (ii) The blend is vitrified. Given that the demixing is not extensive and still far from the thermodynamic limit, and that we also see deterioration in FF (to be discussed more fully below), we conclude that crystallization is a strong contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…[17,53,54] This nucleation would enhance growth of crystals due to the extra chemical potential of the SMA crystals, thus forming large crystals over time by depleting the mixed domains. [59] Nevertheless, as new systems are developed for higher efficiency, it is not clear if higher lifetime can also be achieved and any new hypomiscible polymer:nonfullerene SMA (NF-SMA) systems may suffer from the morphology instability driven by thermodynamics. [47] It has been reported that some nonfullerene acceptors exhibit higher thermal and oxidative stability than the widely explored fullerene acceptors.…”
mentioning
confidence: 99%
“…Organic solar cells (OSCs) are considered as the third generation photovoltaic technology with the advantages of light weight, low‐cost solution processing and mechanical flexibility . Benefitting from the rapid development of photoactive layer materials, the power conversion efficiency (PCE) of single‐junction OSC has exceeded 15%, showing great potential for the practical use of OSCs .…”
Section: Optical Properties and Electrochemical Properties Of The Cilmentioning
confidence: 99%
“…The ITIC‐DM NFA with methyl group substitution showed an obviously increased charge recombination order after aging, while the ITIC‐2F with fluorine substitution showed a slight recombination order charge. The various charge recombination is caused by the different morphological defects or trap‐related recombination in active layer after aging because of their different chemical stability originating from the substitution effect . Recently, Chen et al constructed tandem OSC‐selecting PBDB‐T:F‐M and PTB7‐Th:O6T‐4F:PC 71 BM as the active layers of front and rear cells, respectively (molecular structure as shown in Scheme ).…”
Section: Stability Of Active Layer Materialsmentioning
confidence: 99%